Exploring the Influencing Factors for Contraceptive Use among Women: A Meta-Analysis of Demographic and Health Survey Data from 18 Developing Countries. (14th November 2022) - Islam, Md. Akhtarul; Khan, Md. Nafiul Alam; Raihan, Hasin; Barna, Sutapa Dey
Abstract : Background . The primary objective of this research was to investigate how socioeconomic and demographic factors influence the usage of contraceptives by women in 18 developing countries. Methods . The study used the latest DHS data from 18 developing countries in order to acquire a broad perspective of contraceptive methods. We applied meta-analysis techniques for 18 developing countries to find out the summary results. Results . The overall summary effect showed that the variable respondent education (OR = 1.39 ; 95% CI: 1.17 to 1.65), husband education (OR = 1.60 ; 95% CI: 1.32 to 1.93), type of place of residence (OR = 0.88 ; 95% CI 0.78 to 0.98), current working status (OR = 1.47 ; 95% CI 1.30 to 1.66), age of the respondent (OR = 3.41 ; 95% CI 2.35 to 4.93), breastfeeding status (OR = 1.34 ; 95% CI 1.11 to 1.62), and desire for more children (OR = 0.53 ; 95% CI 0.43 to 0.65) were the significant factors for contraceptive utilization in developing countries. Conclusions . According to the findings of this descriptive study, the respondent's age, level of education, and work status were shown to be the most significant factors that influence the usage of contraceptives in developing countries. It is necessary to take reasonable steps in order to increase the rate of utilizing methods of contraception among women of reproductive age who are uneducated, living in rural areas, and unemployed.